PROTOTYPE DEVELOPMENT OF A TRACEABILITY SYSTEM FOR COCONUT PALM SUGAR SUPPLY CHAIN IN INDONESIA - Elgy Muhammad Rizqya, Kudang Boro Seminar, Agus Buono (International Journal of Research Science and Management, 2017)
Implementation of international regulations on food traceability encourages companies to adapt to the established rules. Consumers are also considered to have the rights to receive safe products with quality as promised. Traceability system is one of the tools to guarantee the quality and safety of a product. The development of technology and information systems become one of the factors that support the development of traceability system, but there are still many companies that have not realized the importance of information and technology for the development and still utilizes paper-based traceability system. The purpose of this research is to design a traceability system using System Development Life Cycle (SDLC) approach utilizing barcode and Radio Frequency Identification (RFID) to be able to store and read products’ data. The users involved in this coconut sugar supply chain study are farmers, collectors, processors, transporter and retailers. The prototype traceability system that has been developed can be used by actors and consumers and other stakeholders, such policy makers or governmental officers to track and trace products from farmers to retailers.